Reserva extrativista (RESEX) Marinha Mãe Grande de Curuçá: gestão ambiental e possibilidade de turismo na comunidade da Vila de Mutucal - TRINDADE, Lione das Neves (2019)
This paper aimed to analyze the relationship between environmental management, tourism and landscape in the RESEX Marinha Mãe Grande de Curuçá, considering the interaction between local community and environment, highlighting environmental management as an important factor for the protection of natural resources, as well as An adequate management of the natural landscape, which is a tourist attraction since this area has a significant tourism potential and a large part of the residents showed interest in developing this activity, it would be a viable alternative, as long as there was an organization , Planning and qualification of the community.